High School Education: What is the Probability of Attending an Official School in Colombia? - Cerquera-Losada , Oscar Hernán; Rodriguez-Corredor, María Camila; Riveros-Pastrana, Linda Mariana (Sociedad y Economía, 2023)
The objective of this paper is to analyze the probability that a high school student has of attending an official school in Colombia, given some sociodemographic and family variables during the years 2009, 2014 and 2019. Quantitative information is available from the ICFES the Saber 11° test. Two types of analysis were performed, on the one hand, the presence of local spatial autocorrelation was examined through the clustering autocorrelation contrast and the Moran index. On the other hand, a Probit probability econometric model was estimated. As for the results, it was observed that students with favorable economic conditions are more likely to attend non-official schools. However, during the last few years, the preference for official schools has been increasing, even in households with higher socioeconomic levels. Additionally, the existence of spatial autocorrelation between departments was validated.